The Role of Social Media in Indonesia’s Political Campaigns: A New Era of Electioneering - Assaefi, Amiluddin; Laskarwati, Batari; Zainurrohmah, Zainurrohmah (Universitas Negeri Semarang, 2024)
This study investigates the transformative impact of social media on political campaigns in Indonesia. With the rapid digitalization of political discourse, social media has become a crucial tool for candidates to engage with voters, shape public opinion, and influence electoral outcomes. This research explores how platforms such as Facebook, Twitter, and Instagram have redefined traditional campaigning methods in Indonesia, fostering new dynamics in political communication, voter mobilization, and the dissemination of information. The study focuses on the increasing prominence of digital strategies in Indonesian elections, particularly during the 2014 and 2019 presidential campaigns. By analyzing campaign materials, social media posts, and public responses, this research highlights how political actors leverage online spaces to create narratives, challenge opponents, and interact directly with the electorate. It also examines the role of